Using WARM Technique in Improving Students’ Speaking Skill at Grade X BB of SMA Negeri 1 Batang Anai - Marjenny Marjenny (English Language Teaching and Research, 2018)
This paper is aimed to know whether the use of WARM technique can give significant effect cognitively, practically and affectively toward students’ skill in speaking at Grade X BB of SMAN 1 Batang Anai. The paper was a writer’s best practice. The instrument of the paper was speaking test. The data were analyzed by comparing students’ speaking test before and after administering the technique. Based on the result of the test and the writer’s observation, it was found that WARM technique gave significant effect toward students’ speaking skill, especially in KD 4.6 namely contrasting simple past and present perfect tense, as it was compared to conventional technique that was usually used by the teacher in teaching speaking. It was proved by the result of the test which showed that (1) the mean score of the students’ speaking test was 82 higher than that which was 74, (2) students participated actively and collaborated integratively in teaching and learning process, (3) the technique accommodated not only extrovert students but also introvert ones (4) the teaching and learning process was fun and enjoyable, and (5) the technique implemented multiliteracies in enhancing students’ character. Based on the result above, it is suggested to English teachers at SMA level to apply this WARM technique as an alternative technique in teaching speaking in English especially and other subjects as well.